PENGARUH METODE DRILL TERHADAP HASIL BELAJAR PRAKARYA BIDANG KERAJINAN PESERTA DIDIK KELAS VII SMP NEGERI 22 PADANG - REPA TAMARA DESI, Drs. Suib Awrus, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of this research to determine the effect of the use of learning learners sebujects prakarya with the focus of the results of learning learners on the class experiment with the class control of the material craft in the VII Junior High School 22 Padang. This type of research is quantitative research.The research conducted in Junior High School 22 Padang on 09 – 30 January 2019. The research instrument is the test of the student learning outcomes. Test result learn of leraners become instrument research. The results of research show the results of leraning learners who taught using the drill method of significantly different with the results of learning learners taught by the provosion of the task (recitation). Basaed on the hypothesis test conducted that the t value = 4.442 and t table = 2.000 then the hypothesis is accepted with a significance value 0,000 < 0,05.Keywords: Drill,excercise, significant